1994
DOI: 10.1017/s0022336000022794
|View full text |Cite
|
Sign up to set email alerts
|

Microforaminiferal linings from the Early Devonian of eastern Australia, and their generic placement

Abstract: Microforaminiferal linings assigned to 10 known genera have been recovered from Early Devonian (Lochkovian to Late Emsian) limestones from Victoria, New South Wales, and Queensland. These organic linings have been identified by comparison with normal-sized agglutinated foraminiferan genera known to occur in the associated sediments. Microforaminiferal linings with smooth walls and reticulate sculptured walls were present and the possible implications of these (diagenetic, relict structure, naked homeomorphs, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…1979), molluscs (Hoare & Farrell 2004; Frýda & Farrell 2005), tentaculitids (Sherrard 1967), crinoids (Jell et al . 1988), foraminiferal linings (Winchester‐Seeto & Bell 1994) and chitinozoans (Winchester‐Seeto 1993). Specimens documented herein were acid‐processed in dilute (10%) hydrochloric acid at the Macquarie University Acid Leaching Facility by Brian D. Johnson in 1981 for his PhD dissertation research from two measured sections (sections G and GC in reference to the ‘Golf Course’), and additional material later recovered via resampling by students at the Macquarie University Centre for Ecostratigraphy and Palaeobiology (MUCEP) at the ‘Golf Course Revisited’ section (GCR in Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…1979), molluscs (Hoare & Farrell 2004; Frýda & Farrell 2005), tentaculitids (Sherrard 1967), crinoids (Jell et al . 1988), foraminiferal linings (Winchester‐Seeto & Bell 1994) and chitinozoans (Winchester‐Seeto 1993). Specimens documented herein were acid‐processed in dilute (10%) hydrochloric acid at the Macquarie University Acid Leaching Facility by Brian D. Johnson in 1981 for his PhD dissertation research from two measured sections (sections G and GC in reference to the ‘Golf Course’), and additional material later recovered via resampling by students at the Macquarie University Centre for Ecostratigraphy and Palaeobiology (MUCEP) at the ‘Golf Course Revisited’ section (GCR in Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…The organic linings of rotalid foraminifera from the Permian to the Recent are well documented (Stancliffe, 1989), but only recently have linings of Palaeozoic agglutinated foraminifera been reported (Winchester-Seeto & Bell, 1994). Continuing study of material from Australia, France, Siberia and Pakistan has shown that Ordovician to Upper Devonian agglutinated foraminiferal organic linings are commonly present in shallow marine limestones, mark and shales.…”
Section: Introductionmentioning
confidence: 99%